PELESAPAN UNSUR KALIMAT PADA JUDUL BERITA KORAN SOLOPOS EDISI SEPTEMBER 2022 - Ja’a Nazielatu Rois Nabila; Siti Aulia Umami; Sumarlam Sumarlam (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
This research is qualitative research with a discourse analysis approach. The purpose of this study is to describe the elements of sentences contained in news headlines in newspapers. The research data used in the form of written text containing the omission of sentence elements. The source of the research data was obtained through the September 2022 edition of the SOLOPOS newspaper. The data was collected by means of a documentation study using reading and note-taking techniques. This research uses analysis technique of agih and insertion. The results showed that the omission of sentence elements contained in the news title of the September 2022 edition of the SOLOPOS newspaper occurred in two elements, namely the omission of the subject and the verb. The process of removing the title on the news is carried out by writers and editors to adjust the layout of small newspapers and make the news more interesting because it arouses the curiosity of readers. The results of the analysis of 10 news headlines found that there were 1 complete sentence that were not omitted and 9 sentences that were omitted by nouns with subject functions, verbs with predicate functions, and affixes to verbs